Dual role of D-amino acid oxidase in experimental pain models - Sharma, Jasmine; Kulshrestha, Ritu; Singh, Nirmal; Jaggi, Amteshwar Singh (European journal of pharmacology, 2019)
D-amino acid oxidase (DAAO) is an astroglial enzyme abundantly present in the pain sensing regions including brain and spinal cord. There have been studies indicating an upregulation and increased activity of DAAO in different pain models. Furthermore, the upregulation of DAAO also results in the development of morphine tolerance as well as morphine-induced hyperalgesia. Accordingly, the knockdown of DAAO gene or pharmacological inhibition of DAAO reduces pain, reverses tolerance to morphine and hyperalgesia. The pain inducing actions of DAAO are related to augmented production of (hydrogen peroxide) H2O2, pro-inflammatory cytokines and activation of (Transient receptor protein Ankyrin-1) TRPA1 channels. On the other hand, exogenously administrated DAAO has also been shown to attenuate the pain in different pain models. The pain attenuating actions of DAAO enzyme has been linked to extensive metabolism of D-serine, which may not be able to activate NMDA receptor and trigger pain. The current review highlights the pain attenuating and pain inducing role of DAAO in experimental studies.